Modification of Petroleum Bitumen with Secondary Polyethylene in the Presence of Vermiculite - Syrmanova Kulash; Kaldybekova Zhanat; Agabekova Aktolkyn; Baizhanova Sholpan; Tuleuov Rassul; Khaldun Al Azzam; El-Sayed Negim; Bounoua Nadia (Indonesian Journal of Chemistry, 2024)
This article presents studies on the modification of petroleum bitumen with polymer waste in the presence of vermiculite. An increase in temperature leads to an increase in the interaction of components, partial breakage of polyethylene and bitumen macromolecules, and the formation of radical-free valences. As a result, fragments of polyethylene and bitumen molecules react with each other, and the formation of qualitatively new structural formations occurs via the strong connection of polar and amorphous bitumen with nonpolar structurally viscous polyethylene. Domestically produced Kulantau vermiculite was used to ensure stable adhesion over a wide temperature range and increase the specific surface area, which acquired additional energy, resulting in an increase in the degree of adhesion to bitumen and increased durability of the binder with improved rheological characteristics. Because of the increased service life of road asphalt pavements, the use of the latter results in a considerable decrease in the cost of polymer-bitumen binders. Based on improved binder formulations, asphalt concrete exhibits excellent water resistance and strength at 50 °C (4.7 to 5.0 MPa). In summary, the modification of bitumen with polymer waste and vermiculite offers a promising avenue for improving the performance and longevity of asphalt pavements.